The Duties and Responsibilities of a Medical Teacher - Reddy, KR (Journal of Gandaki Medical College-Nepal, 2018)
Teachers play vital roles in the lives of the students. Teachers are best known for the role of educating the students. A teacher must be a leader if he/she wants to function effectively in the class room. Teachers set the tone of their class rooms, build a warm environment, mentor and nurture students, and become role models. A teacher is the force that drives the educational system. A teacher is a person who will have to fill many roles. They are people with educational leadership skills and they must continue to grow & develop as professionals. Anyone seeking to be a teacher should take advantage of any chance they get to grow as a person and as a teacher. The most important function of a teacher in the current educational context is managerial function consisting of planning, implementing the plan and controlling the educational process. Planning in education involves formulating educational objectives (departmental and institutional) and planning teaching-learning activities. One of the most important factors in the development and implementation of a teaching – learning program is the leadership style of the teacher. The controlling process in education is called evaluation. Evaluation, not only monitors the progress and achievements of the students, but also provides important information towards modification and improvement of the teaching-learning process. This article pertaining to the discipline of Medical Education discusses some important roles, responsibilities and functions of medical teachers. J-GMC-N | Volume 11 | Issue 01 | January-June 2018, Page: 52-55